A discourse analysis of the Sabah Sarawak Union (SSU), 2011-2015 - Nuriyah binti Akung (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic Universiti Malaysia, 2017)
16 September, 1963 is an important date for Malaysia as it marks the beginning of its existence. On this very date, an agreement was made between United Kingdom of Great Britain and Northern Ireland and the Federation of Malaya (Peninsular Malaysia), North Borneo (Sabah), Sarawak and Singapore allowing all these states to merge and exist as one sovereign state. Focusing on Sabah and Sarawak, a memorandum which is known as the 20 Points Agreement for Sabah and 18 Points for Sarawak was established as to protect the people's interest, rights and autonomy. The emergence of the Sabah Sarawak Union (SSU) in 2011, which claims that the Federal Government has failed to observe these agreements has caused controversy and has become a talking point in the Malaysian political sphere. In the context of this polemic, the SSU has pursued a call for the independence of Sabah and Sarawak from the Federation of Malaysia. This study examines the significance of the existence of the SSU, in the context of its work to realise their political objectives. Also, this study analyses the response of the Government of Malaysia towards the SSU. From the framework of discourse analysis, this study illuminates how the call for independence by the SSU is articulated since its inception in 2011 until 2015. It shows that SSU's independence discourse has successfully drawn the Government's attention, compelling the latter to adopt confrontational engagement, which is explained through the idea of the logic of difference. Up until 2015, the Government and SSU have yet to achieve conciliation. As such, this study, by uncovering the discursive relationship between both sides, proposes ways through which the conflict can be managed better and ultimately be resolved.